Confronting Evil in International Relations
X, 229 p.
Keywords: This book offers original essays on the subject of evil in international relations. It considers questions of moral agency associated with the perpetration of evil acts by individuals and groups in the international sphere, and the range of ethical responses the international community has available to it in the aftermath of large-scale evils.